Microbial risks associated with ready-to-eat foods / Lee Hui Key - Lee , Hui Key (2018)
Numerous reported food poisoning incidents due to microbiological contamination in ready-to-eat (RTE) foods in Malaysia were related to academic institutions. Therefore, this study aimed to (i) examine the microbiological quality of RTE foods, food contact surfaces (FCS), table cleaning cloths (TCC), and food handlers’ hands in the food premises of a public university; (ii) determine the antimicrobial profile, virulence profile and genetic relatedness of bacteria isolated; and (iii) assess the food handlers’ knowledge, attitude and practices (KAP) on food safety. A total of 150 RTE foods, 59 FCS, 34 TCC, and 85 food handlers’ hands swab samples were determined for aerobic colony count (ACC), coliforms, Escherichia coli, Staphylococcus aureus, Salmonella spp., Vibrio cholerae, and Vibrio parahaemolyticus. The bacteria isolated were then characterised by antimicrobial susceptibility testing, virulotyping and genotyping. Sixty-seven (n = 67) food handlers were recruited on the voluntary basis to study the KAP on food safety. Fifty percent (75/150) of the RTE foods harboured an unsatisfactory level of ACC, while 24% (36/150) carried >4 Log CFU/g of coliforms. Salmonella spp. was detected in 33% (50/150) of the RTE foods, 37% (22/59) of the FCS, 62% (21/150) of the TCC and 48% (41/85) of the food handlers’ hands. All RTE foods, 90% of FCS (53/59) and 82% of TCC (28/34) sampled had satisfactory level of Staph. aureus count. Only 5% (3/59), 12% (4/34), and 35% (30/85) of the FCS, TCC and food handlers’ hand, respectively had a satisfactory level of ACC, respectively. The food handlers had moderate food safety knowledge (61.8%), positive attitudes and practices. The education level, working experience and the food safety training course significantly improved the knowledge and attitude of the food handlers (p <0.05). It was noticed that the knowledge on proper food handling practices was not translated into real practices, which results in the poor microbiological quality of the food handlers’ hands, FCS, and the RTE foods prepared. In this study, 130 isolates of E. coli, 81 isolates of Staph. aureus and 26 isolates of V. cholerae were recovered from RTE foods, FCS, TCC and food handler’s hands. All E. coli isolated were non-virulent, but one-third was multidrug resistant. About 97.5% of the Staph. aureus and 88.5% of the V. cholerae strains carried ≥ 1 virulence gene. Cross contamination could have happened among TCC, FCS, and food handlers as 100% similarity among the strains isolated from these samples was observed. This study revealed the high unsatisfactory level of aerobic colony count and Salmonella spp. contamination. The food handlers had poor hand sanitation despite perceiving adequate knowledge, good attitudes and self-reported practices. Therefore, the current safe food handling course needs to be reviewed, and the authority should have a closer monitoring to ensure the food handlers practice proper food handling.